Nickel-based metal-organic framework for non-enzymatic electrochemical sensing of glucose - Che Daud, Nur Aina Diana (2023)
Glucose biosensors have grown in popularity due to their importance in managing diabetes patients' blood glucose levels. Elevated blood glucose levels have the potential to cause acute conditions like diabetes, obesity, and hypertension. These conditions can lead to a substantial financial burden and a diminished quality of life. Consequently, there is a great need for an accurate, quick, and dependable quantitative method of determining glucose concentration. Herein, we report a non-enzymatic glucose sensor based on a metal-organic framework (MOF) as an alternative approach for long-term glucose monitoring. Specifically, nickel-based MOFs were solvothermally synthesized using either 2-amino-1,4- benzenedicarboxylic acid (BDC-NH2) or 2-hydroxy-1,4-benzenedicarboxylic acid (BDC-OH), both of which were characterized by different physicochemical techniques. The electrochemical performance of three electrodes towards glucose sensing was investigated, and Ni-BDC-NH2 exhibited significantly better electrocatalytic behaviour towards the oxidation of glucose than Ni-BDC or Ni-BDC-OH in an alkaline media. This was attributed to a favourable multi-layered sheet-like structure that allowed diffusion for entrapment of glucose and the incorporation of -NH2 functional groups attached to the BDC linker, which were responsible for electrochemical adsorption of glucose molecules. Ni-BDC-NH2 displayed a lower detection limit (3.82 μM), higher stability (>180 days), and remarkable sensitivity (308 μA mM-1 cm-2). Additionally, a molecular sieve effect for Ni-BDC-NH2 led to a noteworthy anti-interference ability, and the sensor displays a fast response time of 5.4 s towards glucose detection. These results indicate that the as-synthesized non-enzymatic glucose sensor operates with a longer lifetime and is viable for use as an intensive monitoring system.